2019
DOI: 10.1253/circj.cj-19-0167
|View full text |Cite
|
Sign up to set email alerts
|

U-Shaped Relationship Between Left Atrium Size on Echocardiography and 1-Year Recurrence of Atrial Fibrillation After Radiofrequency Catheter Ablation ― Prognostic Value Study ―

Abstract: Background: The larger the left atrium anteroposterior dimension (LAD) and left atrium volume (LAV), the stronger the association with recurrent atrial fibrillation (AF) after radiofrequency catheter ablation (RFCA). Patients with a smaller left atrium (LA) size, however, also have increased AF recurrence. Methods and Results: In 521 patients, routine 48-h Holter electrocardiogram and echocardiography were obtained at each outpatient visit every 3 months for 12 months. On multivariate analysis, AF type, LAD, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
2
9
0
Order By: Relevance
“…Our center has previously reported a U-shaped relationship between LAD and AF recurrence, rather than a linear trend. This relationship indicated that medium-sized atria were related to a lower recurrence rate, 19 which is consistent with the results from our study.…”
Section: Ta B L E 5 Univariable and Multivariable Cox Regression Of Asupporting
confidence: 93%
See 1 more Smart Citation
“…Our center has previously reported a U-shaped relationship between LAD and AF recurrence, rather than a linear trend. This relationship indicated that medium-sized atria were related to a lower recurrence rate, 19 which is consistent with the results from our study.…”
Section: Ta B L E 5 Univariable and Multivariable Cox Regression Of Asupporting
confidence: 93%
“…Successful procedure was defined as an efferent block in all pulmonary veins and afferent block in all left atria, which were reconfirmed 30 minutes after the last PVI. Details of the procedure can be obtained from a previous publication from our center 19 …”
Section: Methodsmentioning
confidence: 99%
“…This may due to its association with structural remodeling in AF. A similar conclusion was also found by Mesquita et al 21 and Wang et al 37 Type of AF was a commonly used predictor for AF recurrence prediction in some studies, 7,21,30-33, 38 and these studies indicated that non-PAF patients had a higher risk of recurrence. This conclusion is also compatible with our results, as shown in Supplementary Table 3, where the proportions of patients with non-PAF in the low-, mediumand high-risk groups are 0%, 21.4% and 88.5%, respectively.…”
Section: Discussionsupporting
confidence: 79%
“…LA-B is an independent predictor of AF recurrence. While some studies have shown that the larger or smaller the LA-B has the higher the prevalence of AF recurrence [19][20][21]. We found that the LA-B value varies greatly between 29.54 ± 4.43 mm and 37.70 ± 4.40, rather than staying constant throughout the whole cardiac cycle, which might mean that changes of LA-B value in the cardiac cycle should be taken into account when evaluating radiofrequency ablation in patients with atrial brillation by using the LA-B maximum value.…”
Section: Discussionmentioning
confidence: 99%